Readiness to Use Mediation – Judges’ and Entrepreneurs’ Perspective - Włodzimierz Broński; Marek Dąbrowski; Piotr Sławicki; Michał Wiechetek (Utrecht Law Review)
The aim of the research is to assess the readiness of Polish judges and entrepreneurs to use mediation. This issue has not yet been the subject of in-depth empirical analysis. Online questionnaire research was carried out on a group of n = 150 judges and n = 178 entrepreneurs. The obtained results indicate that the surveyed groups differ in terms of readiness for mediation and in terms of expectations regarding the need to change the applicable legal regulations. It was also shown that sociodemographic variables correlate with readiness to refer cases to mediation and the direction of expectations as regards changes to the legal regulations concerning mediation. The conducted research leads to the conclusion that there are significant differences in readiness for mediation among judges and entrepreneurs, with the level of readiness being significantly higher among judges. In the case of judges, differences in readiness for mediation are related only to gender and the size of the place of residence. In relation to entrepreneurs, readiness for mediation is statistically significantly related to education and work experience. The obtained results also confirm significant differences between judges and entrepreneurs as regards expected legislative changes. The differences between the surveyed professional groups mainly concern the legal regulations concerning the obligation to conduct mediation, the costs of mediation and the popularity of mediation among judges. Entrepreneurs, compared to judges, are in favour of more radical changes in all of the above-mentioned areas.